2021
DOI: 10.1590/s1678-3921.pab2021.v56.02109
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of cowpea resistance to Cowpea aphid-borne mosaic vírus

Abstract: The objective of this work was to evaluate the inheritance of resistance to Cowpea aphid-borne mosaic virus (CABMV) in cowpea (Vigna unguiculata). The study was performed between parental genotypes IT85F-2687 (resistant) and 'BR-14 Mulato' (susceptible), generating F1, F2, and F7 populations and backcrosses with both parental genotypes. CABMV was inoculated on plants from all generations, which were then evaluated through visual inspection and description of characteristic symptoms. A chi-square test was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…The non-parametric Chi-square analysis for testing the goodness-of-fit to simple genetic model has been used in several studies to investigate the mode of inheritance of resistance to viral diseases of cowpea (Quatara and Chambliss 1991;Arshad et al 1998;Orawu et al 2013;Silva et al 2021) and many other legumes (Ogundiwin et al 2002;Sharma et al 2008). Monogenic (Quatara and Chambliss 1991;Silva et al 2021) or digenic inheritance (Barro et al 2016) of virus resistance were mostly reported in cowpea and other legumes. However, in some cases, viral diseases of cowpea were observed to be quantitatively inherited (Orawu et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The non-parametric Chi-square analysis for testing the goodness-of-fit to simple genetic model has been used in several studies to investigate the mode of inheritance of resistance to viral diseases of cowpea (Quatara and Chambliss 1991;Arshad et al 1998;Orawu et al 2013;Silva et al 2021) and many other legumes (Ogundiwin et al 2002;Sharma et al 2008). Monogenic (Quatara and Chambliss 1991;Silva et al 2021) or digenic inheritance (Barro et al 2016) of virus resistance were mostly reported in cowpea and other legumes. However, in some cases, viral diseases of cowpea were observed to be quantitatively inherited (Orawu et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Estudos indicam o melhoramento de espécies de plantas como feijão (Phaseolus vulgaris, Lineu) e sorgo a fim de evitar a instalação e multiplicação dos insetos na cultura. Genótipos de feijão apresentaram maior resistência ao ataque de pulgões provavelmente seguindo a via da antibiose (liberação de algum composto que promove maior mortalidade dos afídeos) (Silva e Bleicher, 2010;Ferreira et al, 2020). Como na maioria dos casos, no Brasil, os afídeos se multiplicam por partenogênese vivípara, mesmo os casos em que adultos aparentemente não foram atingidos, sua prole acabou sendo afetada, já que se desenvolve no interior do adulto.…”
Section: Estratégias De Manejo No Patossistema Afídeo-milho-vírusunclassified